2009
DOI: 10.7863/jum.2009.28.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler Sonographic Features of a Krukenberg Tumor in Pregnancy

Abstract: Krukenberg tumor (KT), defined as an adenocarcinoma that metastasizes to the ovary from different primary tumor sites, 1 has an extremely poor prognosis, with a 5-year survival rate ranging from 12% to 23.4%. 2,3 Gastric cancer has been reported as the most frequent primary source responsible for approximately 50% of KTs. 3 A KT from primary gastric carcinoma very rarely complicates pregnancy, and its early diagnosis is often difficult because the persistent gastrointestinal symptoms mimic the nausea and vomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…5 Diğer yandan bazı çalışmalarda; gebelikte ani ortaya çıkan hirsutizm ve/veya virilizasyonun da Krukenberg tümörü ile ilgili olabileceği belirtilmiştir. Ancak gebelikte daha sık görülen ve benign bir lezyon olan luteoma olasılığı nedeni ile tanıda gecikmelere neden olmuştur.…”
Section: Discussionunclassified
“…5 Diğer yandan bazı çalışmalarda; gebelikte ani ortaya çıkan hirsutizm ve/veya virilizasyonun da Krukenberg tümörü ile ilgili olabileceği belirtilmiştir. Ancak gebelikte daha sık görülen ve benign bir lezyon olan luteoma olasılığı nedeni ile tanıda gecikmelere neden olmuştur.…”
Section: Discussionunclassified
“…This is uncommon in primary ovarian tumors and is useful in discriminating Krukenberg tumors from primary ovarian tumors. However, sonographic observations from existing case reports of Krukenberg tumors commonly describe the tumors as roughly uniform solid masses with a strong echo, but lacking internal nodular structure (3,8). Sonographic observations in the present study revealed an encapsulated pedunculated solid and cystic mass, with multiple hyperechoic nodules in the solid portion, which was in accordance with the MRI and pathological results.…”
Section: Discussionmentioning
confidence: 99%
“…Krukenberg tumors account for 1–2% of all ovarian tumors (2) and the 5-year survival rate for a patient with a Krukenberg tumor ranges between 12 and 23.4% (3). The morbidity of pregnant patients with a Krukenberg tumor is even rarer and the survival rate is usually poor (2–5).…”
Section: Introductionmentioning
confidence: 99%
“…HDliveFlow with HDlive silhouette mode therefore facilitates the spatial visualization of blood vessels, demonstrating their dimensions and the relationships between them. Conventional two‐dimensional color Doppler reveals abundant vascularization, and in the case of Krukenberg tumor it will show the main vessel with a tree‐shaped structure penetrating from the periphery into the central part. However, elucidation of the precise pattern of intratumoral vasculature is easier to achieve using HDlive.…”
Section: Casementioning
confidence: 99%